2013
DOI: 10.1155/2013/701970
|View full text |Cite
|
Sign up to set email alerts
|

Development and Treatments of Inflammatory Cells and Cytokines in Spinal Cord Ischemia-Reperfusion Injury

Abstract: During aortic surgery, interruption of spinal cord blood flow might cause spinal cord ischemia-reperfusion injury (IRI). The incidence of spinal cord IRI after aortic surgery is up to 28%, and patients with spinal cord IRI might suffer from postoperative paraplegia or paraparesis. Spinal cord IRI includes two phases. The immediate spinal cord injury is related to acute ischemia. And the delayed spinal cord injury involves both ischemic cellular death and reperfusion injury. Inflammation is a subsequent event o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 47 publications
3
60
0
Order By: Relevance
“…It was also noticed that astrocytes are one of the major components of the blood-brain barrier and BSB, the dysfunction of which contributed to SIRI and the following neurological outcomes. 35 It has been proposed that the protective function of C5aR antagonism is due to the reduction in C5a-mediated activation of astrocytes in a rat model of amyotrophic lateral sclerosis. 18 In support of this hypothesis, the present study showed that the activation of astrocytes and microglia in the spinal cord tissue increased significantly after SIRI but was markedly inhibited by PMX53 administration.…”
Section: Dissussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also noticed that astrocytes are one of the major components of the blood-brain barrier and BSB, the dysfunction of which contributed to SIRI and the following neurological outcomes. 35 It has been proposed that the protective function of C5aR antagonism is due to the reduction in C5a-mediated activation of astrocytes in a rat model of amyotrophic lateral sclerosis. 18 In support of this hypothesis, the present study showed that the activation of astrocytes and microglia in the spinal cord tissue increased significantly after SIRI but was markedly inhibited by PMX53 administration.…”
Section: Dissussionmentioning
confidence: 99%
“…It has been found that the inflammatory cascade is activated due to SIRI, including neutrophil and neuroglia mobilization and infiltration, as well as elevated levels of inflammatory cytokines, such as tumor necrosis factor-α and interleukin-6. 11 The complement system, a major component of the innate immune system, is constituted by a series of complement components and involved in synapse elimination, 12 development 13 and maturation of neural systems. 14 A range of pathologies in the brain or the spinal cord, including ischemia-reperfusion injury (IRI), 15 stroke, traumatic brain injury and spinal cord injury, 16 potently trigger complement activation following the disruption of neuronal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although various interventions have been reported to prevent or retard SIRI, which still remain unpredictable and unpreventable, current studies suggest that the pathophysiological mechanisms underlying SIRI are complicated, including calcium overload, oxidative stress, excitotoxicity, neuronal apoptosis and the release of inflammatory factor. 2,3 A series of studies 3,4 have revealed that inflammatory activation has a critical role in the progression of SIRI, which include glial response and leukocyte infiltration in the spinal cord. Furthermore, cytokines such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1, IL-6 and IL-10 are all rapidly produced in the spinal cord following SIRI.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cytokines such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1, IL-6 and IL-10 are all rapidly produced in the spinal cord following SIRI. 4 The complement system, a major component of the innate immune system, was constituted by a series of complement components and involved in the neural development, synapse elimination and maturation of neural networks. 5 In addition, in a range of brain or spinal cord pathogenesis, including ischemia reperfusion injury (IRI) or stroke, traumatic brain injury and spinal cord injury, rapid disruption of neuronal homeostasis potently triggers complement activation.…”
Section: Introductionmentioning
confidence: 99%